Peripheral Antinociception Induced by Carvacrol in the Formalin Test Involves the Opioid Receptor-NO-cGMP-K+ Channel Pathway - Mario I. Ortiz; Raquel Cariño-Cortés; Eduardo Fernández-Martínez; Victor Manuel Muñoz-Pérez; Gilberto Castañeda-Hernández; Martha Patricia González-García (Metabolites)
Background/Objectives: Carvacrol is a naturally occurring phenolic monoterpene that is one of the main constituents of the essential oils of oregano (Origanum vulgare) and other herbs. Carvacrol has anti-inflammatory and antinociceptive effects. Carvacrol can activate and inhibit several second messengers and ionic channels at the systemic level. However, there is no evidence of the peripheral antinociception of carvacrol and its mechanism of action. This study was designed to determine whether the opioid receptor-nitric oxide (NO)-cyclic guanosine monophosphate (cGMP)-K+ channel pathway is involved in the local antinociception of carvacrol. Methods: Wistar rats were injected with 1% formalin subcutaneously on the dorsal surface of the right hind paw with the vehicle or carvacrol (100–300 µg/paw). To determine whether the opioid receptor-NO-cGMP-K+ channel pathway and a biguanide-dependent mechanism are responsible for the local antinociception induced by carvacrol, the effect of the injection (10 min before the 1% formalin injection) with the corresponding vehicles, metformin, naltrexone, NG-L-nitro-arginine methyl ester (L-NAME), 1 H-(1,2,4)-oxadiazolo (4,2-a) quinoxalin-1-one (ODQ), and K+ channel blockers on the antinociception induced by local carvacrol (300 µg/paw) was determined. Results: In both phases of the formalin test, carvacrol produced antinociception. Naltrexone, metformin, L-NAME, ODQ, glibenclamide and glipizide (both ATP-sensitive K+ channel blockers), tetraethylammonium and 4-aminopyridine (voltage-gated K+ channel blockers), and apamin and charybdotoxin (Ca2+-activated K+ channel blockers) reversed the carvacrol-induced peripheral antinociception. Conclusions: The local peripheral administration of carvacrol produced significant antinociception and activated the opioid receptor-NO-cGMP-K+ channel pathway.